Advanced Thermochromic Ink System for Medical Blood Simulation - Mohammad Noorizadeh; Abdullah Alsalemi; Yahya Alhomsi; Aya Nabil Khalaf Mohamed Sayed; Faycal Bensaali; Nader Meskin; Ali Ait Hssain (Membranes, 2021)
Simulators for extracorporeal membrane oxygenation (ECMO) have problems of bulky devices and low-fidelity methodologies. Hence, ongoing efforts for optimizing modern solutions focus on minimizing expenses and blending training with the intensive care unit. This is particularly evident following the coronavirus pandemic, where economic resources have been extensively cut. In this paper, as a part of an ECMO simulator for training management, an advance thermochromic ink system for medical blood simulation is presented. The system was developed and enhanced as a prototype with successful and reversible transitions between dark and bright red blood color to simulate blood oxygenation and deoxygenation in ECMO training sessions.